An extended MARCOS method for MCGDM under 2-tuple linguistic q-rung picture fuzzy environment. (April 2023) - Akram, Muhammad; Khan, Ayesha; Luqman, Anam; Senapati, Tapan; Pamucar, Dragan
Abstract: The current study is mainly devoted to explore and extend the measurement and ranking of alternatives according to the compromise solution under the background of 2-tuple linguistic q -rung picture fuzzy sets. The capability of q -rung picture fuzzy sets to accommodate a broad range of information, and the salient features of 2-tuple linguistic term sets to manage qualitative data motivate us to present the notion of 2-tuple linguistic q -rung picture fuzzy set. The linguistic terms are very useful to deal with the situations where the data providing the assessment of attributes are not easily quantified. This paper proposes and utilizes the Dombi operations to develop certain aggregation operators: 2-tuple linguistic q -rung picture fuzzy Dombi weighted averaging operator and 2-tuple linguistic q -rung picture fuzzy Dombi weighted geometric operator. The presented methodology utilizes the aforementioned operators to handle and aggregate data in decision-making problems. Furthermore, an example to select the best option among the collection of considered projects is handled through the proposed method to substantiate the extended approach. Ultimately, the validation of the developed technique is conducted through a comparative analysis.